2000
DOI: 10.1046/j.1365-2427.2000.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and ecological traits of benthic freshwater macroinvertebrates: relationships and definition of groups with similar traits

Abstract: Summary Relating species traits to habitat characteristics can provide important insights into the structure and functioning of stream communities. However, trade‐offs among species traits make it difficult to predict accurately the functional diversity of freshwater communities. Many authors have pointed to the value of working with groups of organisms as similar as possible in terms of relationships among traits and have called for definition of groups of organisms with similar suites of attributes. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
372
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(393 citation statements)
references
References 42 publications
17
372
0
4
Order By: Relevance
“…Charvet et al (2000), Usseglio-Polatera et al (2000), and Gayraud et al (2003) indicate the enhanced usefulness of functional diversity in the biological assessment of different European watercourses when compared with other measures of diversity of benthic animals. Roque et al (2014) found noticeable differences between traditional diversity measures and distinctness in prediction abilities to different environmental variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charvet et al (2000), Usseglio-Polatera et al (2000), and Gayraud et al (2003) indicate the enhanced usefulness of functional diversity in the biological assessment of different European watercourses when compared with other measures of diversity of benthic animals. Roque et al (2014) found noticeable differences between traditional diversity measures and distinctness in prediction abilities to different environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Faith and Baker, 2006) and functional diversity based on the analysis of the biological traits of benthic animals (e.g. Usseglio-Polatera et al, 2000;Statzner et al, 2005). These components of diversity provide certain additional value to theoretical and applied ecology (Mason et al, 2005;Schweiger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…between different catchments, Usseglio-Polatera et al 1999, or upstream-downstream of an organic pollution, Usseglio-Polatera et al 2000), but always in the surface assemblages. In this study, we used this approach for interstitial fauna with poor results, certainly because major constraints that shape interstitial assemblages (e.g.…”
Section: Changes In Bio-ecological Groupsmentioning
confidence: 96%
“…35. USSEGLIO-POLATERA et al (2000), on their assay of grouping benthic freshwater macroinvertebrates following common biological/ecological traits had Porifera and Bryozoa clustered together on account of they being filter feeders, sessile and producers of asexual resistant bodies. On the other hand STUART & KLUMPP (1984), upon a study of particle-size selection and foodresource partitioning among marine benthic filter feeders which commonly depend on the suspended particulate organic material in the media (an ascidia, 3 bivalves and a sponge) demonstrated that: "a mixed assemblage of sponges and bivalves may be able to utilize the suspended material more efficiently than a single-species population, due to recycling of some of the particles".…”
Section: Corvoheteromeyenia Heterosclera (Ezcurra Dementioning
confidence: 99%